A Case of Congenital Dyserythropoeitic Anemia Type IV Caused by E325K Mutation in Erythroid Transcription Factor KLF1. Issue 6 (August 2018) - Ortolano, Rebecca; Forouhar, Melissa; Warwick, Anne; Harper, David
Abstract : Congenital dyserythropoetic anemias (CDA) represent a heterogeneous group of inherited red cell disorders resulting in ineffective erythropoiesis. Several CDA variants have been identified. KLF1 is a transcription factor required for cell division in erythroid differentiation and maturation, and the switch from fetal to adult hemoglobin. Mutations in KLF1 gene can result in a wide range of phenotypes. This case illustrates the E325K mutation in KLF1 presenting with severe anemia in infancy, persistently elevated fetal hemoglobin, and progressive improvement with age. This case of CDA because of KLF1 mutation highlights the common features and expected disease course of CDA type IV.